Предмет: Математика,
автор: paramonova78
как решить 5/6:(5/6х - 5/6) - 5/6 = 5/6
Ответы
Автор ответа:
0
5/6:(5/6х - 5/6) = 5/6+5/6
5/6:(5/6х- 5/6) = 10/6
5/6х- 5/6 = 5/6:10/6
5/6х- 5/6 = 5/6 * 6/10
5/6х- 5/6 = 1/1 * 1/2
5/6х = 5/6+1/2
5/6х = 5/6+3/6
5/6х = 8/6
х = 8/6 : 5/6
х = 8/6 * 6/5
х = 8/5
х = 1 3/5 3/5 = 6/10 = 0,6
х = 1,6
5/6:(5/6х- 5/6) = 10/6
5/6х- 5/6 = 5/6:10/6
5/6х- 5/6 = 5/6 * 6/10
5/6х- 5/6 = 1/1 * 1/2
5/6х = 5/6+1/2
5/6х = 5/6+3/6
5/6х = 8/6
х = 8/6 : 5/6
х = 8/6 * 6/5
х = 8/5
х = 1 3/5 3/5 = 6/10 = 0,6
х = 1,6
Похожие вопросы
Предмет: Литература,
автор: danilovdanil418
Предмет: Математика,
автор: ekanidovazanna
Предмет: Литература,
автор: gkulmagambetova96
Предмет: Алгебра,
автор: Lizkkka
Предмет: Математика,
автор: JuliaBr